Second language skills for all? : analyzing a proposed language requirement for U.S. Air Force officers - Hardison, Chaitra M. (Technical report (Rand Corporation), 2012)
Would it be feasible to require all Air Force officers to attain a specific level of proficiency in a second language at commissioning? Would there be unintended consequences? To find out, the authors asked Air Force officers about their own language-learning experiences, what they thought about language learning and mandatory language proficiency policies, what incentives and disincentives they perceived, among other questions. While the officers felt language proficiency was important for mission success, they were not convinced about its importance for career success. They also noted that the time and commitment required to attain proficiency might interfere with other, more pressing academic demands. The languages most have studied already are not among those most critical to national security, and those who were required to study a language considered themselves less proficient than those who had studied it voluntarily. Language skills were, however, associated with other desirable outcomes, such as greater interest in and tolerance of other cultures and being interested in and capable of learning another language in the future. But requiring all to attain such proficiency before commissioning would mean fewer would be eligible for it. Instead, we suggest implementing a variety of pre- and post-commissioning language-learning incentives and opportunities designed to accommodate learners at all levels (from those just starting out to those who are at more advanced levels) and to increase acquisition of underrepresented and strategic languages. Career-long policies for maintaining and increasing language proficiency would be needed to make pre-commissioning and early career efforts worthwhile.